125k views
4 votes
Prove that 1 - cosx / sinx = sinx / 1 + cosx
how?

User Rossisdead
by
4.5k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

using the identity

cos²x = 1 - sin²x

consider the left side


(1-cosx)/(sinx)

multiply numerator/ denominator by (1 + cosx)

=
((1-cosx)(1+cosx))/(sinx(1+cosx)) ← expand numerator

=
(1-cos^2x)/(sinx(1+cosx))

=
(sin^2x)/(sinx(1+cosx)) ← cancel sinx on numerator/ denominator

=
(sinx)/(1+cosx)

= right side , thus proven

User Aqn
by
5.6k points